The Effect of Centella asiatica Methanolic Extract on Expression of IL-1β Proinflammatory Cytokines in Severe Early Childhood Caries - Luthfi, Muhammad; Razak, Fathillah Abdul; Kusumawardhani, Devy Putri; Nagoro, Ayu Anggraini Broto; Fadhila, Naura (European Journal of Dentistry, 2022)
Objective This article analyzes the role of C. asiatica extract in reducing the proinflammatory cytokine interleukin (IL)-1β produced by salivary neutrophils.Material and Methods Selected kindergartens in the Surabaya area provided samples. The sample was initially checked for dental caries by measuring its def-t index, and then the participants who satisfied the requirements for severe caries with a def-t of greater than 6 were chosen. At the time of sampling, all of the individuals were between the ages of 4 and 6. The sampling was performed by researchers and certified persons using well-known methodologies. For 60 minutes before to sampling, respondents were not allowed to eat, drink, chew gum, or brush their teeth. For analysis, the samples were collected and then frozen at −80°C.Results The administration of methanolic extract C. asiatica decreased the expression of the proinflammatory cytokine IL-1β on the surface of salivary neutrophils on S-ECC; The administration of C. asiatica methanol extract resulted in a decrease in the expression of the proinflammatory cytokine IL-1β on the surface of salivary neutrophils in S-ECC.Conclusion C. asiatica extract has the effect of reducing the proinflammatory cytokine IL-1β produced by salivary neutrophils on S-ECC via inhibiting nuclear factor kappa B and mitogen–activated protein kinase signaling pathway activation and suggest that C. asiatica is a possible candidate for treating S-ECC.
Keywords: Centella asiatica; S-ECC; IL-1β; chronic diseases; medicine